2013
DOI: 10.1257/pol.5.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Federal Policy to Insure Young Adults: Evidence from the 2010 Affordable Care Act's Dependent-Coverage Mandate

Abstract: Using data from the Survey of Income and Program Participation (SIPP), we study the health insurance and labor market implications of the recent Affordable Care Act (ACA) provision that allows dependents to remain on parental policies until age 26. Our comparison of outcomes for young adults aged 19–25 with those who are older and younger, before and after the law, shows a high take-up of parental coverage, resulting in substantial reductions in uninsurance and other forms of coverage. We also find preliminary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
237
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(250 citation statements)
references
References 23 publications
10
237
3
Order By: Relevance
“…This means that our results do not capture effects of that provision, which has been well studied in previous research. [11][12][13][14][15][16] Similarly, our analysis does not estimate coverage gains from early Medicaid expansions that began in 2010 and 2011, which were generally much more limited than the 2014 changes. 17 Our sample excluded adults 65 years of age or older, who are overwhelmingly enrolled in Medicare and thus ineligible for the coverage expansion under the ACA.…”
Section: Discussionmentioning
confidence: 95%
“…This means that our results do not capture effects of that provision, which has been well studied in previous research. [11][12][13][14][15][16] Similarly, our analysis does not estimate coverage gains from early Medicaid expansions that began in 2010 and 2011, which were generally much more limited than the 2014 changes. 17 Our sample excluded adults 65 years of age or older, who are overwhelmingly enrolled in Medicare and thus ineligible for the coverage expansion under the ACA.…”
Section: Discussionmentioning
confidence: 95%
“…This provision took effect September 2010. We do not examine this policy here, since it had essentially reached steady-state by 2012 and has already been examined thoroughly elsewhere (Antwi, Moriya, & Simon, 2013). 4 been largely descriptive (Cohen & Martinez, 2014;Long et al, 2014) or limited to a particular aspect of the ACA such as the Medicaid expansion (Black & Cohen, 2015;Kaestner, Garrett, Gangopadhyaya, & Fleming, 2015;Wherry & Miller, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The broader academic literature has also concluded that the provision generated substantial gains in young adult coverage, though estimates vary across studies, with some estimates higher than ASPE's and others lower (Cantor et al 2012;Antwi, Moriya, and Simon 2013;Porterfield and Huang 2016).…”
Section: Expanding Access To Coverage For Young Adultsmentioning
confidence: 99%